Synthesis of novel functional liquid and its application as a modifier in SBR/silica composites (eXPRESS Polymer Letters, 2010)
A novel functional ionic liquid (IL), 1-methylimidazolium methacrylate (MimMa), was synthesized for modifying styrene butadiene rubber (SBR)/silica composites. MimMa was found to be readily polymerized via the initiated radical mechanism and could be analogously grafted onto rubber chains during vulcanization. Substantial hydrogen bonding between polymerized MimMa (poly(MimMa)) and silica can facilitate the silica dispersion and improve the SBR/silica interfacial bonding. Filler networking, curing behavior, silica dispersion and mechanical performance of the modified SBR/silica composites were studied. With a low concentration of MimMa, remarkable improvements in the interfacial interactions and mechanical properties were achieved which was attributed to the improved silica dispersion and strengthened interfacial bonding induced by MimMa. A modified interphase structure was accordingly proposed and related to the mechanical performance of the modified SBR/silica composites.